KEBUDAYAAN, KEKERABATAN DAN PERANTAUAN: Catatan Atas Tesis Yang Deterministik - Budi Rajab (Jurnal Masyarakat dan Budaya, 2004)
In general, research on the migration process of the Minangkabau people evolve around two theses. First, the migration is caused by matrilineal kinship system in which the status and position of male is inferior to that of female. Second, Minangkabau community has a cultural mission that idealizes a desire for male to migrate in order to seek wealth and to gain new knowledge that their homeland cannot provide. However, both theses have profound weaknesses. On the first thesis, if it is true that matrilineal kinship system has driven male to migrate, then in an ethnic group with patrilineal kinship system the contrary should have taken place. But that is not the case. In both kinship systems the majority of migrating people are men. On the second thesis, ia a community that has no cultural mission about the purpose of migration, in fact, people still tend to migrate. A study conducted by the writer concluded that both matrilineal kinship system and cultural mission only play as intervening variables which have increased the size of the migration. The main determinant remains rural-urban imabalances in economic development that have attracted people to move to cities.